Peningkatan Pengetahuan Siswa Kelas VII dan Penurunan Skala Nyeri Dismenora Primer Menggunakann Video Senam Dismenorhea - Nurvadila, Putri; Virawati, Dini Indo; Satriani, Satriani (Jurnal Kebidanan Malakbi, 2023)
False information regarding menstruation has the potential to cause a variety of emotions, including worry, dread, and confusion. Worrying about getting their period or experiencing menstrual discomfort, particularly if they consider these events to be common rites of passage. By informing young girls about the typical causes of discomfort during their period, it may be possible to enhance their mental health. This research intends to demonstrate how a dysmenorrhea exercise plan may help reduce symptoms by quantifying pain on a visual analog scale. In this research, a single-group pretest-posttest format was employed using a pre-experimental design. The Wilcoxon test had 35 female students in total, and the significance level was fairly low. The findings suggest that the knowledge of the respondents may be biased. Before seeing the video, 11 respondents (31.4%) scored 67 points, while the same set of respondents (34.34%) scored 87 points on the post-test. The dysmenorrhea exercise video is effective since there is a correlation between responder knowledge and pain levels (p=0.000 on the pain scale). According to updated sources, when modified in light of recommendations for further research, dysmenorrhea exercise is expected to prove to be an effective method for lowering discomfort and encouraging movement.